The impact of protein quality on the promotion of resistance exercise-induced changes in muscle mass. Issue 1 (December 2016) - Phillips, Stuart
Abstract Protein supplementation during resistance exercise training augments hypertrophic gains. Protein ingestion and the resultant hyperaminoacidemia provides the building blocks (indispensable amino acids – IAA) for, and also triggers an increase in, muscle protein synthesis (MPS), suppression of muscle protein breakdown (MPB), and net positive protein balance (i.e., MPS > MPB). The key amino acid triggering the rise in MPS is leucine, which stimulates the mechanistic target of rapamycin complex-1, a key signalling protein, and triggers a rise in MPS. As such, ingested proteins with a high leucine content would be advantageous in triggering a rise in MPS. Thus, protein quality (reflected in IAA content and protein digestibility) has an impact on changes in MPS and could ultimately affect skeletal muscle mass. Protein quality has been measured by the protein digestibility-corrected amino acid score (PDCAAS); however, the digestible indispensable amino acid score (DIAAS) has been recommended as a better method for protein quality scoring. Under DIAAS there is the recognition that amino acids are individual nutrients and that protein quality is contingent on IAA content and ileal (as opposed to fecal) digestibility. Differences in protein quality may have important ramifications for exercise-induced changes in muscle mass gains made with resistance exercise as well as muscle remodelling. Thus, the purpose of this review is a critical appraisal of studies examining the effects of protein quality in supplementation on changes in muscle mass and strength as well as body composition during resistance training.